The Problem of Perfection: Reflections on Heaven and Human Nature - Petrik, James (Ye.A.Buketov Karaganda State University Publ., 2014)
In the present paper analyzes the current issue of improvement of human nature and is closely associated with the presence of all sorts of evil in the world. Without going into the history of the subject, the author examines two different points of view, trying to find something in common that unites, links and unites them. However, the point of view — religious, where God is regarded as the most perfect being, but a person only his likeness. Another stresses the need for the infinite perfection of human nature, the development of it as a spiritual and moral being. However, as the author concludes that a person should not rely solely on the heavens, and count on myself, objectively assessing their own strength and to set realistic goals.
Кемелдік мəселесі: Құдай жəне адамзат табиғаты туралы ой-толғамдар
Проблема совершенства: размышления о Боге и человеческой природе
Keywords: еxistence; transcendent; human; experience; nature; problem